Publication trend of TMPRSS2 as SARS-CoV-2 receptor during the COVID-19 pandemic - Lalu Muhammad Irham; Dyah Aryani Perwitasari; Yudha Rizky Nuari; Wirawan Adikusuma; Haafizah Dania; Rita Maliza; Made Ary Sarasmita; Rocky Cheung; Adi Wira Septama (Universitas Ahmad Dahlan, 2023)
The Coronavirus Disease 2019 (COVID-19) pandemic has not yet been fully under public health control, which is still currently impacting a large number of people worldwide in 2023. Since the pandemic emerged, the growing number of publications related to TMPRSS2 as a SARS-CoV-2 receptor worldwide has increased rapidly with various findings and qualities. It is important to determine the trend of TMPRSS2 publication as no such studies currently exist that represent the publication trend related to this critical field of study. Here, we employed a bibliometric-based approach to evaluate the research trends of TMPRSS2 mechanistically as the SARS-CoV-2 receptor. We identified 1012 research documents published between 2020 and 2022 for this study. The most common document category was